Estudio anatómico de órganos vegetativos en Datureae (Solanaceae) - Liscovsky, Iris Josefina (2002)
Anatomical study of the vegetative organs in species of Datureae (Solanaceae). This study deals with the leaf and stem anatomy in species of Datureae G. Don: Brugmansia x candida Pers., B. suaveofens Bercht. & Presl., Oatura ferox L., O. inoxia MilI.. O. metef L., O. stramonium var. stramonium L., O. stramonium varo tatufa (L.) Torr., O. wrightii Hort. ex Regel. The stem features support the point of view that Oatura L. and Brugmansia Pers. should be considered independent but closely related genera.